Assessing Public Participation in Maine: The Old and the New in Civic Involvement - Platt, David (Maine Policy Review, 1992)
Lack of citizen participation in American government is a complaint frequently voiced by politicians, political scientists and media commentators. The steady decline in voting, the rising number of Americans who say they are disaffected with their government, and the increase in two-earner households all have been cited as evidence of this decreased involvement by Americans in public life. Maine, with its long tradition of participatory democracy, reflected in town meeting government at the local level, is not necessarily a microcosm of what is occurring nationally. The state has, however, experienced its share of some of the civic maladies note nationally, according to David Platt, a veteran Maine print and broadcast journalist, who was asked by Maine Policy Review to gauge civic involvement in Maine communities. Among other things, Platt found that non-conventional, participatory approaches to public life are being attempted. Some innovators are trying to create ways in which grassroots organizing can be used for developing realistic alternatives rather than being employed merely to prevent bad or unpopular public policy decisions from being implemented.
Keywords: Maine; civic engagement; volunteerism